Hyaluronan oligosaccharides induce cell death through PI3-K/Akt pathway independently of NF-κB transcription factor - Alaniz, L. (2006)
Several studies indicate that hyaluronan oligosaccharides (oHA) are able to modulate growth and cell survival in solid tumors; however, no studies have been undertaken to analyze the effect of oHA on T-lymphoid disorders. In this work we showed that oHA were able to induce apoptosis in lymphoma cell lines. Since PI3-K/Akt and nuclear factor-κB (NF-κB) are major factors involved in cell survival and anti-apoptotic pathways in lymphoma cells, we hypothesized that oHA could induce apoptosis through inhibition of these pathways. oHA were identified by a method which allows characterization of length using a high pH anion exchange chromatography with pulse amperometric detection (HPAEC-PAD). oHA inhibited PIP3 production (principal product of PI3-K activity) and reduced Akt phosphorylation levels, similarly to the specific inhibitor wortmannin. However, treatment with either oHA or wortmannin failed to inhibit constitutive NF-κB activity and modulate IκBα protein levels, suggesting that PI3-K and NF-κB signaling pathways are not related in the cell lines used. Cell behavior differed using native hyaluronan (HA), which induced PIP3 production, Akt phosphorylation, and NF-κB activation, although not related with cell survival since treatment with native HA showed no effect on apoptosis. Our results suggest that oHA induce apoptosis by suppression of PI3-K/Akt cell survival pathway without involving NF-κB activation, through a mechanism that differs from the one mediated by native HA. © 2006 Oxford University Press.